AN OVERVIEW OF THE LANDSCAPE OF ADULTS WITH DISABILITIES IN SINGAPORE. A LITERATURE REVIEW - Eunice Meng Yin Tan, Ivy Chia (EPRA International Journal of Multidisciplinary Research (IJMR), 2023)
Children with disabilities grow up and become adults. In Singapore and the rest of the world, there is a lack of research on adults. In 2017, the National Council of Social Services (NCSS) in Singapore, conducted and piloted a study about the Quality of Life for adults with disabilities. It was conducted employing the WHOQOL (World Health Organisation Quality of Health) assessment to better understand the needs of vulnerable adults, including persons with disabilities. In this study, 1,000 persons (adults) with disabilities aged 18 and above were surveyed. It was found in this study that persons with disabilities want to feel enabled and to live their lives as independently as possible. These adults that were surveyed also conveyed that they wanted easier and seamless access to information and pertinent services, including receiving appropriate social support and developing the confidence of participants as active members of society.